Histological and Immunohistochemical Features of Pulmonary Metastatic Oral Melanoma in a Labrador dog - Behra, Biswadeep; Vairamuthu, S; Pazhanivel, Natesan; Jalantha, Periyasamy; Rao, Ganne Venkata Sudhakar (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Melanoma is a malignant tumour that originates from melanocytes. It has been reported in human beings as well as in many domesticated animal species (Reddy et al., 1998), and wild terrestrial and marine animals. Melanomas are the most commonly diagnosed malignant tumours in the oral cavity of canines (Goldschmidt, 1985; Faramade et al., 2017). Gingiva is the most common site for canine oral malignant melanoma (OMM) but other parts like palatine, labile or buccal mucosa also act as the sites of origin (Delverdier et al., 1991). It is generally an aggressive tumour, often locally invasive, and frequently metastasizes to regional lymph nodes and lungs but metastasis to other organs like the brain, heart, spleen, and liver is not common (Goldschmidt and Hendrick, 2002). Canine OMM accounts for about 7% of all malignant tumours of canine, 11.5% to 17.1% of all oral tumours (Mikiewicz et al., 2019), and 33% to 35.8% of all malignant oral tumours (Sarowitz et al., 2017). OMM is reported in old age group animals mainly ranging from 7 to 14 years age (Esplin, 2008). Most common breeds affected by OMM include Cocker Spaniels, Golden Retrievers, Dachshunds, mixed-breed dogs (Gillard et al., 2014) but histologically well-differentiated melanocytic neoplasms (HWDMN) also reported in Golden Retrievers, Labrador, Doberman Pinscher, Irish Setters, Cocker Spaniels, Beagles, etc. (Esplin, 2008). The diagnosis of melanoma is difficult mainly in tumors without appreciable melanin. Histological appearance resembles carcinoma, lymphoma, sarcoma, and osteogenic tumours. Therefore, immunohistochemistry with numerous melanoma specific markers is mostly used for confirmatory diagnosis in human and veterinary pathology (Wick, 2008). This case report is on the occurrence of oral melanoma with pulmonary metastasis in a Labrador dog.